2021
DOI: 10.1021/acs.jchemed.0c01497
|View full text |Cite
|
Sign up to set email alerts
|

Prompts to Promote Success: Evaluating Utility Value and Growth Mindset Interventions on General Chemistry Students’ Attitude and Academic Performance

Abstract: Some students struggle with chemistry because they do not find the relevance between chemistry content and their lives or they perceive their intelligence as fixed. Social-psychological interventions (SPIs), brief interventions that target students’ subjective experiences, were developed to address these issues. As a result, SPIs have been associated with gains in students’ academic performance, attitude, and persistence in various instructional settings; however, only a limited number of studies have explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 59 publications
(179 reference statements)
1
34
1
Order By: Relevance
“…The data comprised students’ test scores used to answer the first research question and students’ written responses to the UVI prompts to answer the second and third research questions. The reliance on three prompts and the design of the utility value and construct summary prompt were similar to Wang et al; however, the use of extra credit as an incentive differed from the prior work which integrated the prompts into homework assignments.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data comprised students’ test scores used to answer the first research question and students’ written responses to the UVI prompts to answer the second and third research questions. The reliance on three prompts and the design of the utility value and construct summary prompt were similar to Wang et al; however, the use of extra credit as an incentive differed from the prior work which integrated the prompts into homework assignments.…”
Section: Methodsmentioning
confidence: 99%
“…An extensive literature base supports the effectiveness of UVIs in terms of improving students’ course achievement, persistence, and affective outcomes (e.g., students’ interest). ,− The settings vary from high school to college level classes including courses such as psychology, physics, algebra, biology, and chemistry. ,,,, Recently, the effectiveness of UVIs in several studies conducted in college level STEM courses was summarized by Wang et al . However, only two studies have implemented UVIs within chemistry courses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on studies, immediate feedback to students is the most beneficial rather than a few days, weeks, or months later (Schmulian & Coetzee, 2019). In Wang et al, (2021) study, they discovered that individuals who got prompt feedback improved their academic performance much more than those who received delayed feedback. Similarly, Dhawan (2020), confirmed that students who received a lot of instant feedback were better able to grasp their lessons.…”
Section: Providing Immediate Feedbackmentioning
confidence: 99%